The System Approach in the Perspective of Law Number 20 of 2003 concerning the National Education System - Siraj, Siraj; Nasrah, Sayni; Trisfayani, Trisfayani (Universitas Malikussaleh, 2019)
In the context of implementing decentralization in the education sector, there are many problems that arise, because the implementation of decentralization of education is different from the decentralization of other areas of government which is basically concentrated at the district and city level. Decentralization of education has not only stalled at the district and city level but even more so that it reaches the school level. The existence of autonomy in the management of education is a potential for schools to improve the performance of personnel, offer direct participation from relevant parties, and increase public understanding of the implementation of education in schools. Decentralization of education has encouraged the improvement of services in the field of education to the community, which leads to efforts to improve the quality of education management at the lowest level, namely schools through the implementation of School-Based Management. The implementation of School-Based Management in general is to empower or empower schools through giving authority to schools, giving schools greater flexibility to manage school resources, and encouraging the participation of school members and communities to improve the quality of education.